(untitled) (Fiep Bulletin - online, 2014)
The art of mountain climbing goes back to primordial times; climbs were done to worship the gods; today, man climbs the highest mountains as a form of pleasure, seeking the enjoyment of beating the challenges that mountain climbing offers.Imposing, beautiful, powerful, and somehow influencing the human lifestyle, mountains always brought great fascination to human beings. Today these adventurers climb the highest and most dangerous mountains in search of pleasure; however, this pleasure is preceded by uncertainties as to the results or consequences; transcending these uncertainties, a sensation of pleasure invades, swallows and overpowers the climber and he sees himself united to the sensation that, in the beginning, was external, but now takes over his entire body, leading him to ecstasy.